Thermoregulatory burden of elite sailing athletes during exercise in the heat: A pilot study - van Delden, M.; Bongers, C. C. W. G.; Broekens, D.; Daanen, H. A. M.; Eijsvogels, T. M. H. (Temperature, 2019)
Exercising in a hot and humid environment increases core body temperature, which may limit exercise performance. The risk of exercise-induced hyperthermia and associated performance decrement in Olympic sailing athletes is largely unknown. Therefore, this study aimed to compare thermoregulatory responses and performance indicators of elite sailors in a cool versus hot and humid environment. Seven elite athletes from four different Olympic sailing classes (Laser, RS:X, Finn, 470) performed cycling and/or rowing exercise in a cool (18°C) and hot (33°C) environment, while core body temperature (TC), skin temperature (TSK), exercise performance (covered distance), and rating of perceived exertion were measured continuously. TC increased significantly more in the hot environment (37.6 ± 0.2°C to 39.1 ± 0.1°C) compared to the cool environment (37.5 ± 0.1°C to 38.5 ± 0.2°C; p = 0.002), but the increase in TC between conditions differed substantially within individuals (range: 0.3°C - 0.9°C). Exercise performance decreased by 6.2 ± 2.9% in the hot environment (p = 0.013, range: 2.3%-9.5%), but more importantly, exercise performance was strongly inversely related to peak TC (R = -0.78, p = 0.039). Rating of perceived exertion (cool: 14.2 ± 0.6; hot: 13.9 ± 1.2) and increase in TSK (cool: 0.5 ± 1.0°C; hot: 0.9 ± 0.3°C) did not differ between conditions (p = 0.59 and p = 0.36, respectively). To conclude, a larger increase in TC and substantial exercise performance decrement were observed in the hot versus cool environment. As a further matter, large inter-individual differences were observed across athletes with an inverse relationship between TC and exercise performance, which stresses the importance of appropriate and personalized interventions to reduce thermoregulatory burden of elite sailors during exercise in the heat.